(untitled) (Journal of Intellectual Property Rights (JIPR), 2026)
The study explores the evolution of patent damages and its transformative nature in Indian jurisprudence, with a focus on compensation and deterrence mechanisms. Historically, Indian courts have been hesitant to award substantial damages, favoring injunctions due to limited precedents and challenges in quantifying losses. Recent landmark judgments by the Delhi High Court, alongside the Intellectual Property Division Rules of 2022, signal a shift towards more structured damage calculations, including lost profits, royalty rates, and aggravated damages. By comparing practices in India, the US, and Europe, this paper highlights the growing alignment of Indian courts with global standards. These developments strengthen patent enforcement, incentivize innovation, and set a critical precedent for intellectual property law in India.